Turbidity and suspended solids removal from high-strength wastewater using high surface area adsorbent: Mechanistic pathway and statistical analysis. Issue 1 (31st December 2016) - Amosa, Mutiu Kolade; Jami, Mohammed Saedi; Alkhatib, Ma'an Fahmi R.; Tajari, Tamrin; Jimat, Dzun Noraini; Owolabi, Rasheed Uthman
Abstract: In this study, the potential of an improved empty fruit bunch-based powdered activated carbon (PAC) with high surface area was employed in removing suspended solids and turbidity from a high-strength wastewater. Also, the effects of operating parameters, such as PAC dosage, contact time and mixing speed on sorption trends of the two pollutants from the wastewater—biotreated palm oil mill effluent using a full factorial experimental design was investigated. Adsorption efficiency of 89.1 and 91.4% were observed for suspended solids and turbidity, respectively, at the operating condition of 3.5 g PAC dosage, 45 min contact time and 150 rpm mixing speed. The analysis of variance also revealed that the actual and model predicted values were in agreement with R 2 values of 0.9949 and 0.9991 for suspended solids and turbidity, respectively. The three operating factors had similar significance on the sorption of both pollutants with an increasing sequence of significance: contact time < mixing speed < PAC dosage. This is indicative of their similar mechanistic pathway and response trends to the adsorption process. The Freundlich and pseudo-second-order models also predicted the experimental data in describing the adsorption behaviour with R 2 values of 0.9057 and 0.9998.